Learning with Partially Labeled and Interdependent Data - Amini, Massih-Reza.; Usunier, Nicolas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book develops two key machine learning principles: the semi-supervised paradigm and learning with interdependent data. It reveals new applications, primarily web related, that transgress the classical machine learning framework through learning with interdependent data. The book traces how the semi-supervised paradigm and the learning to rank paradigm emerged from new web applications, leading to a massive production of heterogeneous textual data. It explains how semi-supervised learning techniques are widely used, but only allow a limited analysis of the information content and thus do not meet the demands of many web-related tasks. Later chapters deal with the development of learning methods for ranking entities in a large collection with respect to precise information needed. In some cases, learning a ranking function can be reduced to learning a classification function over the pairs of examples. The book proves that this task can be efficiently tackled in a new framework: learning with interdependent data. Researchers and professionals in machine learning will find these new perspectives and solutions valuable. Learning with Partially Labeled and Interdependent Data is also useful for advanced-level students of computer science, particularly those focused on statistics and learning.
Introduction -- Introduction to learning theory -- Semi-supervised learning -- Learning with interdependent data.
Keywords: Computer science; Data mining; Artificial intelligence; Statistics; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Electronic books